Local Fish-Based Nutritious Menu Innovation for Stunting Prevention through Posyandu Cadre Capacity Strengthening in Sungai Piring - Yessi Alza; Roziana Roziana (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Stunting remains a significant global public health challenge. In 2024, an estimated 23.2% of children under five, approximately 150.2 million globally, were affected by stunting, defined as height-for-age below −2 standard deviations of the WHO Child Growth Standards. Although Indonesia has demonstrated a downward trend in stunting prevalence, declining from 24.4% in 2021 to 21.6% in 2022 and 19.8% in 2024, the rate remains above the national target of 14% for accelerated stunting reduction, indicating the need for sustained multisectoral interventions. Strengthening community-based strategies that utilize locally available animal protein sources, such as fish, is essential. Posyandu cadres play a strategic role in delivering nutrition education and influencing child feeding practices at the grassroots level.Aims: This community engagement program aimed to strengthen posyandu cadres’ capacity in stunting prevention through nutrition education and innovation of nutrient-dense local fish–based complementary food (fish floss/abon ikan).Methods: The program was conducted on 20 September 2025 at Posyandu Durian, Tasik Raya Village (Sungai Piring Health Center area), involving 20 cadres. Activities included structured nutrition education and a hands-on demonstration of fish floss preparation. Knowledge improvement was assessed using pre- and post-tests.Results: The average knowledge score increased from 65 (pre-test) to 84 (post-test), representing a 29% improvement. Cadres acquired practical skills in processing locally available fish into an acceptable complementary food, which was well received by mothers and toddlers.Conclusion: Integrating participatory education with practical food innovation effectively strengthened cadres’ competencies and demonstrates potential as a sustainable community-driven strategy for supporting long-term stunting prevention